2017
DOI: 10.3390/en11010055
|View full text |Cite
|
Sign up to set email alerts
|

Battery Dimensioning and Life Cycle Costs Analysis for a Heavy-Duty Truck Considering the Requirements of Long-Haul Transportation

Abstract: Abstract:The use of heavy-duty battery electric trucks for long-haul transportation is challenging because of the required high energy amounts and thus the high capacity of traction batteries. Furthermore a high capacity battery implies high initial costs for the electric vehicle. This study investigates the required battery capacity for battery electric trucks considering the requirements of long-haul transportation in Germany and compares the life cycle costs of battery electric trucks and conventional diese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 12 publications
2
67
0
Order By: Relevance
“…As many other studies, they also concluded that the main energy source for vehicular application and transportation is based on fossil fuels in the foreseeable future [18]. There is growing interest towards full electrification of vehicles and recently more studies have been carried out for understanding better the cost structure of electric powertrains in heavy vehicles [19,20]. Based on these studies, the charging infrastructure has an important influence on the vehicle operating performance and lifecycle costs.…”
Section: Technology Assessment Of Alternative Powertrainsmentioning
confidence: 92%
See 1 more Smart Citation
“…As many other studies, they also concluded that the main energy source for vehicular application and transportation is based on fossil fuels in the foreseeable future [18]. There is growing interest towards full electrification of vehicles and recently more studies have been carried out for understanding better the cost structure of electric powertrains in heavy vehicles [19,20]. Based on these studies, the charging infrastructure has an important influence on the vehicle operating performance and lifecycle costs.…”
Section: Technology Assessment Of Alternative Powertrainsmentioning
confidence: 92%
“…Electrical components can be large, especially when considering heavy-duty Besides higher development costs, there are some technical weaknesses related to electric powertrains. Electrical components can be large, especially when considering heavy-duty applications [20]. For example, a traction motor typically requires an inverter that also takes quite a lot of space in relation to the motor.…”
Section: Electric and Hybrid Powertrainsmentioning
confidence: 99%
“…Since 80% of all trips are shorter than 600 km (Fries, ), the indicated range of the Tesla Semi is 800 km is sufficient for most of the daily trips of a European long‐haul truck. A 150 kW charging system is able to charge the battery in less than 9 h and, thus, completely during the driver's daily rest periods (Mareev, Becker, & Sauer, ). An average utilization of the charging system of 8 h per day (Gnann et al., ) and 240 working days per year is assumed.…”
Section: Methodsmentioning
confidence: 99%
“…The necessary drive power is determined using the driving resistance model, which is based on following equations [30,31,21]:…”
Section: Driving Resistance Modelmentioning
confidence: 99%